2014
DOI: 10.4103/0253-7613.129312
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Tinospora cordifolia ethanol extract on 6-hydroxy dopamine induced Parkinsonism

Abstract: Objective:The present study investigates the neuroprotective activity of ethanol extract of Tinospora cordifolia aerial parts against 6-hydroxy dopamine (6-OHDA) lesion rat model of Parkinson's disease (PD).Materials and Methods:T. cordifolia ethanol extract (TCEE) was standardized with high performance thin layer chromatography using berberine. Experimental PD was induced by intracerebral injection of 6-OHDA (8 μg). Animals were divided into five groups: sham operated, negative control, positive control (levo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…T . cordifolia ethanol extract exhibited significant neuroprotection by increasing the dopamine levels (1.96 ± 0.20 and 2.45 ± 0.40 ng/mg of protein) and complex I activity (77.14 ± 0.89 and 78.50 ± 0.96 nmol/min/mg of protein) at 200 and 400 mg/kg, respectively [ 87 ]. Combination of ethanolic extracts of T .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…T . cordifolia ethanol extract exhibited significant neuroprotection by increasing the dopamine levels (1.96 ± 0.20 and 2.45 ± 0.40 ng/mg of protein) and complex I activity (77.14 ± 0.89 and 78.50 ± 0.96 nmol/min/mg of protein) at 200 and 400 mg/kg, respectively [ 87 ]. Combination of ethanolic extracts of T .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…However, neuroprotective activity of this plant is least explored. Recently, the ethanolic extract of T. cordifolia was reported to exhibit neuroprotective activity against 6-OHDA induced Parkinsonism [ 15 ]. Recent studies from our lab have reported that 50% aqueous ethanolic extract of T. cordifolia (TCE) ameliorated anxiety, improved exploratory behavior and modulated synaptic plasticity in sleep-deprived rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with its radio- and chemoprotective effects, T. cordifolia has also been reported to show neuroprotective potential by modulating anti-oxidant enzyme system of brain tissue 10 . Oral dose of ethanolic extract of T. cordifolia has been found to enhance the dopamine level and complex-I activity in 6-hydroxy dopamine (6-OHDA) induced Parkinson model of rat along with reduced oxidative stress and improved locomotor activity 11 . Petroleum ether extract of T. cordifolia has been reported to reverse the depression-like behavior in mice and reduced the monoamine oxidase activities in the brain, resulting in increased levels of brain monoamines 12 .…”
mentioning
confidence: 99%